Bambo Can Go - Tramer, Maciej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The author analyses Tuwim’s Bambo, the Black Boy and tries to point to a number of interpretative paradoxes that have accumulated around its multiple readings. Particular attention is paid to the racial readings of the poem. What is more, the author discusses a variety of contemporary contexts in which the famous poem functions; these are often politically incorrect readings and interpretations which make no sense of the historical context in which the work was originally written. The article offers a detailed analysis of the origins of the poem and the circumstances in which found its way to the school primer. The poem is seen as expressing the need for accepting otherness and fighting cultural stereotypes.